Sr–Nd–Pb–Hf Isotopic Constraints on the Mantle Heterogeneities beneath the South Mid-Atlantic Ridge at 18–21°S - Yun Zhong; Xu Zhang; Zhilei Sun; Jinnan Liu; Wei Li; Yaoliang Ma; Weiliang Liu; Bin Xia; Yao Guan (Minerals, 2020)
In an attempt to investigate the nature and origin of mantle heterogeneities beneath the South Mid-Atlantic Ridge (SMAR), we report new whole-rock Sr, Nd, Pb, and Hf isotopic data from eight basalt samples at four dredge stations along the SMAR between 18°S and 21°S. Sr, Nd, and Pb isotopic data from SMAR mid-ocean ridge basalts (MORBs) at 18–21°S published by other researchers were also utilized in this study. The SMAR MORBs at 18–21°S feature the following ratio ranges: 87Sr/86Sr = 0.70212 to 0.70410, 143Nd/144Nd = 0.512893 to 0.513177, 206Pb/204Pb = 18.05 to 19.50, 207Pb/204Pb = 15.47 to 15.71, 208Pb/204Pb = 37.87 to 38.64, and 176Hf/177Hf = 0.283001 to 0.283175. The 87Sr/86Sr, 143Nd/144Nd, 206Pb/204Pb, and 176Hf/177Hf ratios of these MORBs varied considerably along the SMAR axis. The variable compositions of the Sr–Nd–Pb–Hf isotopes, combined with the corresponding whole-rock major and trace elemental abundances reported in previous studies, suggest that the SMAR MORBs at 18–21°S were probably derived from a heterogeneous mantle substrate related to a mixture of depleted mantle (DM) materials with a small amount (but variable input) of HIMU (high-μ, where μ = 238U/204Pb)- and enriched (EMII)-type materials. The HIMU-type materials likely originated from the proximal St. Helena plume and may have been transported through “pipe-like inclined sublithospheric channels” into the SMAR axial zone. The EMII-type materials possibly originated from a recycled metasomatized oceanic crust that may have been derived from the early dispersion of other plume heads into the subcontinental asthenosphere prior to the opening of the South Atlantic Ocean. In addition, the contributions of subducted sediments, continental crust, and subcontinental lithospheric mantle components to the formation of the SMAR MORBs at 18–21°S may be nonexistent or negligible.